2022
DOI: 10.1111/cen.14828
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of acromegaly is higher than previously reported: Changes over a three‐decade period

Abstract: Objective To study time‐related changes in the prevalence and patient characteristics of acromegaly, as well as to assess the impact of changes in treatment on disease control. Methods A total of 107 patients with acromegaly were identified by healthcare registries and subsequently validated by patient chart review over a three‐decade period (1992–2021). A systematic literature review focusing on the incidence and prevalence of acromegaly was performed identifying 31 studies. Results The prevalence of acromega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(112 reference statements)
2
7
0
Order By: Relevance
“…The prevalence and incidence of acromegaly in the present study are in line with previous estimates from the Nordic countries [ 4 , 5 , 26 29 ], indicating a good coverage of the patient population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence and incidence of acromegaly in the present study are in line with previous estimates from the Nordic countries [ 4 , 5 , 26 29 ], indicating a good coverage of the patient population.…”
Section: Discussionsupporting
confidence: 92%
“…Acromegaly is a chronic disease caused by excessive secretion of growth hormone (GH) most often from a somatotroph pituitary adenoma, with subsequently increased levels of insulin-like growth factor 1 (IGF-1) [ 1 ]. Based on recent studies, the estimated prevalence is 28–137 cases/million inhabitants and the incidence varies between 2–11 cases/million per year [ 2 5 ], hence acromegaly is considered an orphan disease as defined by the European Union ( European Medicines Agency , 02.09.2019). The clinical manifestations of acromegaly are caused by systemic effects related to the prolonged exposure to GH/IGF-1 excess (musculoskeletal, cardiovascular and metabolic comorbidities) and the local tumor extension (visual-field defects, cranial-nerve palsy and hypopituitarism) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In actual study, we included consecutive patients with respect of inclusion/exclusion criteria, that were diagnosed for acromegaly between 2012 and 2017. Interestingly, Aagaard and coauthors recently reported data on the prevalence of acromegaly in the last three decades, providing an increased frequency of acromegaly in females, with a prevalence of 42% between 1992 and 2001 and of 66% between 2012 and 2021 44 . The higher number of females patients included in the current study may reflect also differences in tumor dimensions.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, Aagaard and coauthors recently reported data on the prevalence of acromegaly in the last three decades, providing an increased frequency of acromegaly in females, with a prevalence of 42% between 1992 and 2001 and of 66% between 2012 and 2021. 44 The higher number of females patients included in the current study may reflect also differences in tumor dimensions. A gender difference in tumor size was reported in somatotropinomas, in absence of univocal and conclusive results.…”
Section: ≥15% and < 3% 32 (52)mentioning
confidence: 95%
“…The availability of medical alternatives has reduced the use of pituitary tumor irradiation and, in turn, reduced irradiation-induced adverse effects such as secondary intracranial tumors, cerebrovascular disease, and hypopituitarism ( 20 ). The diverse treatment options allow for a more personalized and multimodal treatment approach, leading to disease control in ~60%–90% of patients ( 4 , 6 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%